2003
DOI: 10.1016/s0960-9822(03)00506-2
|View full text |Cite|
|
Sign up to set email alerts
|

Tuberous Sclerosis Complex Gene Products, Tuberin and Hamartin, Control mTOR Signaling by Acting as a GTPase-Activating Protein Complex toward Rheb

Abstract: We show that Rheb acts as a novel mediator of the nutrient signaling input to mTOR and is the molecular target of TSC1 and TSC2 within mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
880
2
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,059 publications
(911 citation statements)
references
References 48 publications
(6 reference statements)
20
880
2
9
Order By: Relevance
“…See text for a more detailed description. Tee et al, 2003). dRheb overexpression recapitulates dTSC1/2 mutant phenotypes, and reduction in dRheb function rescues larval lethality caused by loss of dTSC1/2 in the fly .…”
Section: Introductionmentioning
confidence: 92%
“…See text for a more detailed description. Tee et al, 2003). dRheb overexpression recapitulates dTSC1/2 mutant phenotypes, and reduction in dRheb function rescues larval lethality caused by loss of dTSC1/2 in the fly .…”
Section: Introductionmentioning
confidence: 92%
“…As a heterodimer, TSC1 and TSC2 repress cell growth by inhibiting cell signal transduction through the mammalian target of rapamycin complex 1 (mTORC1) pathway. 12 TSC1/TSC2 possesses GTPase-activating protein (GAP) activity towards the small G-protein, Ras homologue enriched in brain (Rheb), [13][14][15][16] converting Rheb from its active GTP-bound form to the inactive GDP-bound form. Consequently, inactivation of Rheb by TSC1/TSC2 prevents activity of mTORC1 and phosphorylation of the mTORC1 substrates 4E-BP1 and S6K1, leading to repression of protein translation.…”
Section: Introductionmentioning
confidence: 99%
“…Along with others, we showed that the small GTPase Rheb is the molecular link between TSC1/2 and mTORC1. Rheb activates mTORC1, and TSC2 inhibits Rheb by acting as a GTPase-activating protein (Castro et al, 2003;Garami et al, 2003;Tee et al, 2003;Inoki et al, 2003a;Zhang et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%